Childbirth; A traumatic event for women in Pakistan - Syed, Bushra; Zahid, Yumna; Saleem, Zunaira (Journal of the Pakistan Medical Association, 2025)
To the editor, Childbirth is a beautiful experience that millions of women go through worldwide. A woman goes through a rollercoaster of emotions throughout the pregnancy, and one of the most recurring thoughts in a mother’s mind is the event of labour and delivery. Although many have the privilege of having a near-perfect experience, this is not true for many women in Pakistan. Despite being the most cost-effective, only 15% of women choose government setups, most prefer private providers, which can be more expensive, or opt for midwives or untrained staff which although affordable, can have dire consequences [1]. Research indicates that approximately 1.5% of women may experience post-traumatic stress disorder (PTSD) as a consequence of their childbirth experience [2]. Although PTSD can be due to several reasons, many women report a lack of empathy from the healthcare workers, which can directly or indirectly lead to PTSD. The process of giving birth can be very traumatizing in some parts of the world, especially in government hospitals in 3rd world countries like Pakistan. Abuse during childbirth can be of any nature, ranging from physical, verbal, or emotional abuse leading up to disrespect, neglect, or coercion. According to a study conducted across the Sindh province in Pakistan, approximately 97% of women reported experiencing at least one form of disrespectful and abusive behaviour during childbirth [3]. Another study found that poorer women, those less educated on birth preparedness and postnatal care, and those who lacked social support were more vulnerable to mistreatment during childbirth [4]. All the abuse leaves the mother traumatized, which can result in severe mental health disorders, including post-traumatic stress disorder, postpartum depression, and postpartum psychosis. A scoping review concluded that women who reported at least one type of disrespect and abuse were 1.6 times more likely to experience postpartum depression [5]. This is one of the many reasons why women in Pakistan don’t seek out proper maternal care. To address the issue, medical and nursing colleges should have a module on medical ethics which should focus on the importance of informed consent, respect for autonomy, and cultural sensitivity. A robust feedback system should be established to allow patients to report complaints. Public awareness campaigns should be held, and regular audits should be conducted in hospitals to find out the gaps in quality healthcare. Lastly, policies should be made to make public healthcare setups more reliable and accessible to patients.